ARABIC ETHNIC HOUSES IN KAMPUNG ARAB PASAR KLIWON AS THE PRODUCT OF ACCULTURATION - Najmi Muhamad Bazher (Universitas Sebelas Maret Surakarta, 2018)
The wave of migration to Indonesia cause multiculturalism in their communities. Acculturation happened when the imigrant’s culture meet and blend with the native’s culture. Hadhrami immigrants came and stayed in Indonesia, bringing their original culture from Yaman. Islam as their religion became the important part of their life and effecting the culture, wherever they live. Adapting to the native culture and local condition was needed when they chose to settle in Indonesia. Dutch colonization at that time effected Indonesian society’s way of life, so are the immigrants. Socio-cultural dynamics will influence and expressed by architecture form. The objective of this study was to identify acculturation between Arab, Islam, Indonesia, and Dutch culture on architecture of Arab’s ancient houses in Kampung Arab Pasar Kliwon. Research method used in this study is qualitative-explorative and using descriptive as analysis method. Acculturation between Arab, Islam, Indonesia, and Dutch cultures on the Arab’s ancient houses in Kampung Arab Pasar Kliwon, found through the existence of Arab vernacular architecture, islamic concept architecture, tropical-humid architecture, and Dutch colonial architecture on the design program, interior elements, and exterior elements.